Rectal adenocarcinoma in an 9 year old girl. A case report - Hedayatollah Nahvi; Sara Memarian; Mohammadtaghi Majnoon; Behdad Gharib; Mohammad Es-hagh Rozeh; Mojtaba Gorji; Somayeh Jafrasteh; Zeinab Najafi; Rahman Khosravi (Pediatric Surgery Research Center of Shahid Beheshti University of Medical Sciences, 2018)
Rectal adenocarcinoma is rare in children. The patient described here is a 9-year-old girl who presented with rectorrhagia. Her problem started 3 months ago and she had been treated for infectious diarrhea. A colonoscopy was performed 3 months after the onset of symptoms and a non-pedunculated polyp in the rectum was noted and resected. After the colonoscopy signs and symptoms of peritonitis developed and in laparotomy a rectal perforation was noted and a biopsy from rectal mucosa was taken. The result of biopsy was adenocarcinoma. Then a low anterior resection of rectum with protective ileostomy followed by adjuvant chemotherapy was performed. During a 15 month follow-up the patient had no problems and no clinical, radiological or laboratory signs or symptoms of recurrence was found. However rectal adenocarcinoma is rare but it should be considered in the differential diagnosis of intestinal problems.